2006
DOI: 10.1590/s0104-66322006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction (SFE) of rice bran oil to obtain fractions enriched with tocopherols and tocotrienols

Abstract: -Parboiled rice bran oil was obtained with supercritical CO 2 at temperatures and pressures varying from 25 to 60ºC and from 150 to 250 bar, respectively. This study was divided into two different parts: initially, the experiments were carried out with one separation step. In the second part, experiments were performed with two separators in series. The temperatures and the pressures of the first separator were 25 and 40ºC, and 100 and 150 bar. The second separator was maintained at 2ºC and 25bar. This procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Supercritical CO 2 (SC-CO 2 ) allows fast and efficient extractions of oils that deteriorate less and demand less refinement to remove undesirable contaminants than oils extracted using conventional nonpolar solvents. Brazilian Journal of Chemical Engineering has pusblished a series of articles on the use of the technology for the extraction of vegetable oil from rice bran (Sarmento et al, 2006), wheat germ (Zacchi et al, 2006) and macadamia nuts (Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical CO 2 (SC-CO 2 ) allows fast and efficient extractions of oils that deteriorate less and demand less refinement to remove undesirable contaminants than oils extracted using conventional nonpolar solvents. Brazilian Journal of Chemical Engineering has pusblished a series of articles on the use of the technology for the extraction of vegetable oil from rice bran (Sarmento et al, 2006), wheat germ (Zacchi et al, 2006) and macadamia nuts (Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kuk and Dowd 32 reported that the concentration of γ-oryzanols in SC-CO 2 extracted RBO was higher than in RBO derived from hexane-Soxhlet extraction. Another study showed that RBO extracted using SC-CO 2 contained high levels of tocopherols and tocotrienols, suggesting that the oil as a good source of natural vitamin E 33 . However, although SC-CO 2 has shown some potential for extraction of high quality RBO, understanding the influence of extraction parameters as well as material preparation are factors to be considered in achieving the best benefits from rice functional compounds.…”
Section: Supercritical Carbon Dioxide Extractionmentioning
confidence: 99%
“…In addition to being used for total fat quantification, the extraction parameters pressure, temperature, time, and modifier in supercritical fluid extraction can be manipulated to selectively extract particular compounds from sample matrices into the oil fraction. The study by Sarmento s group 33 investigated the influence of temperature 25-60 and pressure 15-20 MPa in extracting RBO to obtain fractions enriched with tocopheol and tocotrienol.…”
Section: Sc-co 2 Extraction Of Rbomentioning
confidence: 99%
“…Liu et al [50] found 50°C and 15 MPa as the optimal condition to obtain total tocopherols from pomegranate. Finally, Sarmento et al [51] identified 40°C and 20 MPa to obtain total tocols from parboiled rice bran. With regard to carotenoids, Wijngaard et al [39] made an extensive review on the SFE conditions and found that the extraction occurs at temperatures between 50-100°C and pressures between 30-40 MPa.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%